Essentials of psychiatric mental health nursing : a communication approach to evidence-based care - Varcarolis, Elizabeth M. (St. Louis, Mo. : Elsevier/Saunders, 2013)
This focused approach to psychiatric mental health provides you with an uncomplicated way to understand the often-intimidating subject of psychiatric nursing. Inside you'll find two themes of psychiatric mental health nursing: the How of Communication and the Why of Evidence. You will also find easy-to-understand explanations of the research that applies to psychiatric nursing issues and how to incorporate this evidence into everyday care.
UNIT I: ESSENTIAL THEORETICAL CONCEPTS FOR PRACTICE -- UNIT II: TOOLS FOR PRACTICE OF THE ART -- UNIT III: CARING FOR PATIENTS WITH PSYCHOBIOLOGICAL DISORDERS -- UNIT IV: COMMUNICATING WITH AND PLANNING CARE FOR PATIENTS EXPERIENCING PSYCHIATRIC EMERGENCIES -- UNIT V: COMMUNICATING WITH AND PLANNING CARE FOR PATIENTS WITH DESCRETE NEEDS
Includes bibliographic references and index.
Keywords: EVIDENCE-BASED NURSING; MENTAL DISORDERS -- NURSING